A micropatterned elastomeric surface with enhanced frictional properties under wet conditions and its application. Issue 45 (30th October 2017) - Ko, H.; Seong, M.; Jeong, H. E.
Abstract : A new type of micropatterned surface with arch-shaped microstructures with superior wet frictional properties is proposed with a demonstration of its practical application to automated substrate transportation systems. Abstract : Engineered surfaces that have high friction under wet or lubricated conditions are important in many practical applications. However, it is not easy to achieve stable high friction under wet conditions because a layer of fluid prevents direct solid–solid contact. Here, we report a micropatterned elastomeric surface with superior wet friction. The surface has unique arch-shaped microstructures arrayed in a circle on the surface to provide high friction on wet or flooded surfaces. The arch-shaped micropatterned surface exhibits remarkably enhanced and stable friction under wet conditions, surpassing even the performance of the hexagonal patterns of tree frogs, owing to the large contact surface and the optimal shape of drainage channels. Robotic substrate transportation systems equipped with the micropatterned surfaces can manipulate a delicate wet substrate without any sliding in a highly stable and reproducible manner, demonstrating the superior frictional capabilities of the surface under wet conditions.